UNCOVERING INTENT: REASSESSING THE ROLE OF MOTIVE IN THE PUNISHMENT OF PREMEDITATED MURDER IN INDONESIA - Christine, Christine; Kristiawanto, Kristiawanto; Teepapal, Tanawat (PENA LAW: International Journal of Law, 2025)
The sentencing of premeditated murder cases in Indonesia has so far emphasized the elements of planning and the consequences of the act, but has paid little attention to the perpetrator's motive as a reflection of the degree of culpability. In many progressive legal systems, however, motive is considered important in assessing the extent to which criminal intent (mens rea) contributes to the quality of a criminal act. This study aims to reassess the role of motive in the sentencing of premeditated murder under Article 340 of the Criminal Code, and to propose an evaluative model that can be used to enhance substantive justice in Indonesia's criminal justice practice. Using a legal-normative method and a qualitative approach to twenty court decisions selected purposively (period 2018–2024), it was found that in 70% of cases, motive was not considered as a legal factor in the court’s decision. Motives were merely mentioned in the chronology without legal weight. However, in criminal law practice in Germany and the Netherlands, motives serve as the basis for classifying murder and determining criminal sanctions. This study developed a conceptual model that categorizes motives into three categories: rational-emotional, manipulative-opportunistic, and pathological, each with its own evaluative implications for sentencing. This study recommends that motives be integrated into national sentencing guidelines and incorporated into judicial training based on contextual justice. In this way, Indonesia's sentencing system can become more humane, fair, and aligned with the values of substantive justice.